Implementação de game para tablet como mediador de ensino e aprendizagem do ciclo de vida das borboletas para crianças - D'Oliveira, Patrícia Aparecida Brigola Vargas (2020)
The objective of this dissertation was to emphasize the contributions of mediation of a game for tablet with children. To this end, a game was designed and implemented in an attempt to contribute to the teaching-learning process on the subject “life cycle of butterflies” for science teaching mediated by technological resources. In addition, it also seeks to evaluate technological mediation as a tool for teaching science. From the initial bibliographic review, the theoretical bases for conducting the research were established. Methodologically, a theoretical review was carried out preceded by the elaboration of a game and strategies for its applicability in the classroom, with elementary school students. Then, the activity of observation and intervention with students was carried out, using the tablet, from a game about the life cycle of butterflies, as well as the considerations that led to their results. The mediation of scientific knowledge was made possible to students through the game, emphasized as an important teaching-learning tool. In the activity carried out, the students showed interest, attention and knowledge sharing, since, when passing the stage, they sought to help colleagues who were still at previous levels. In addition, through observation and subsequent analysis of drawings produced by students on the metamorphosis of the butterfly, the success of the activity was noticeable, proving the relevance of using games to mediate scientific knowledge in the school context.